1D and 2D NMR studies of 2–(2–(BENZYLOXY)–3–METHOXYPHENYL)–1H–BENZIMIDAZOLEF - Al–Douh, Mohammed Hadi; Abdul Hamid, Shafida; Osman, Hasnah (Universitas Gadjah Mada, 2007)
The reaction of Benzyl o–vanillin 1 and o–phenylene diamine 2 in dichloromethane produced new benzimidazole, 3. The complete assignments of 3 were made using 1D and 2D NMR including COSY, HMQC and HMBC NMR in CDCl3 and acetone–d6. The coupling constants J are reported in Hertz, and the differences in the peak splittings using both solvents are discussed